Sex-dependent monoamine oxidase isoforms expression patterns during human brain ageing - Sanfilippo, Cristina; Castrogiovanni, Paola; Imbesi, Rosa; Lazzarino, Giuseppe; Di Pietro, Valentina; Li Volti, Giovanni; Tibullo, Daniele; Barbagallo, Ignazio; Lazzarino, Giacomo; Avola, Roberto; Musumeci, Giuseppe; Fazio, Francesco; et al. (Mechanisms of ageing and development, 2021)
Human behavior is influenced by both genetic and environmental factors. Monoamine oxidase A (MAOA) is among the most investigated genetic determinants of violent behaviors, while the monoamine oxidase B (MAOB) is explored in Parkinson's disease. We collected twenty-four post-mortem brain tissue datasets of 3871 and 1820 non-demented males and females, respectively, who died from causes not attributable to neurodegenerative diseases. The gene expressions of MAOA and MAOB (MAO genes) were analyzed in these subjects, who were further stratified according to age into eleven groups ranging from late Infancy (5-9 months) to centenarians (>100 years). MAO genes were differently expressed in brains during the entire life span. In particular, maximal and minimal expression levels were found in early life and around the teen years. Females tended to have higher MAO gene levels throughout their lives than those found in age-matched males, even when expressions were separately measured in different brain regions. We demonstrated the existence of age- and sex- related variations in the MAO transcript levels in defined brain regions. More in-depth protein studies are needed to confirm our preliminary results obtained only on messenger RNAs in order to establish the role played by MAO genes in human development.
Keywords: Infant; dospělí; Gene Expression Regulation, Enzymologic; Monoamine Oxidase; senioři nad 80 let; mozek; předškolní dítě; monoaminoxidasa; Brain; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Sex Characteristics; regulace genové exprese enzymů; mužské pohlaví; Aging; Child, Preschool; Adult; Adolescent; Infant, Newborn; novorozenec; ženské pohlaví; lidé; mladiství; dítě; Child; Aged; senioři; pohlavní dimorfismus; Male; kojenec; stárnutí; Female